Cover volume 1 ebook - Bendis, Brian Michael (Cover, 2022)
New York Times bestselling writer Brian Michael Bendis and creator of the bestselling Kabuki series David Mack, team up to tell an incredible new espionage epic in COVER. Based on a true story, the intelligence community figures out that the traveling band of social misfits who make comic books are an exact match to the profiles of candidates recruited for intelligence and counterintelligence gathering. A well-known comics creator is recruited by the agency to live a double life as a spy. And convention season is upon us. Collects issues #1-#6 with a brand-new cover by David Mack!